Local Agricultural Product Packaging Innovation as an Effort to Improve Branding and Sustainable Excellence of Farmer Community Products in Ciburial Village, West Bandung Regency - Fitriani Reyta; Susan Purnama; Bob Foster (Britain International for Academic Research (BIAR) Publisher, 2024)
The Joint Partners of Farmer Groups (Gapoktan) in Ciburial Village, West Bandung Regency, has great potential in selling horticultural agricultural products, one of the Gapoktans already has potential market demand is Cipta Mandiri. Gapoktan Cipta Mandiri has a high demand for organic vegetable products, digital media marketing increases awareness and expands the market quickly. The high demand creates new problems for Gapoktan Cipta Mandiri, namely product packaging that is not yet able to protect the product for long distance delivery, while consumer demand is not only from Bandung and its surroundings, as well as other large cities that are pretty far away, packaging innovations are needed that can protect the durability of organic vegetables, which are accessible from chemicals, where product spoilage is faster than non-organic products. Vacuum packaging innovations with cooling and anti-rotting systems need to be developed to support market demand which is already quite rapid. This innovation is expected to increase the potential for economic independence in other Ciburial village communities besides Gapoktan Cipta Mandiri. This research aims to determine the role of organic agricultural product packaging innovation in improving the branding and sustainable excellence of Gapoktan agricultural products. Ciburial Village, West Bandung Regency. A total of 100 samples were used from a population of 200 organic vegetable consumers in large cities, consisting of online consumers of organic products from Gapoktan Cipta Mandiri, Ciburial. The results of packaging innovation are proven to increase brand awareness and knowledge as well as the superiority of agricultural products by 78.25%. The branding strength formed from packaging innovation increases the product's competitive advantage by 85.16%. The indirect influence through the variable between branding has a path coefficient value that is greater than the direct influence path coefficient value. The branding strategy increases the impact of the packaging innovation strategy on the competitive advantage of Ciburial Village Gapoktan MSME products.